Neuroinflammation of microglia polarization in intracerebral hemorrhage and its potential targets for intervention - Yang, Guoqiang; Fan, Xuehui; Mazhar, Maryam; Guo, Wubin; Zou, Yuanxia; Dechsupa, Nathupakorn; Wang, Li (Frontiers in molecular neuroscience, 2022)
Microglia are the resident immune cells of the central nervous system (CNS) and play a key role in neurological diseases, including intracerebral hemorrhage (ICH). Microglia are activated to acquire either pro-inflammatory or anti-inflammatory phenotypes. After the onset of ICH, pro-inflammatory mediators produced by microglia at the early stages serve as a crucial character in neuroinflammation. Conversely, switching the microglial shift to an anti-inflammatory phenotype could alleviate inflammatory response and incite recovery. This review will elucidate the dynamic profiles of microglia phenotypes and their available shift following ICH. This study can facilitate an understanding of the self-regulatory functions of the immune system involving the shift of microglia phenotypes in ICH. Moreover, suggestions for future preclinical and clinical research and potential intervention strategies are discussed.
Gesehen am 11.09.2023